BODY MASS INDEX WITH SYSTOLIC AND DIASTOLIC BLOOD PRESSURE AT A PUBLIC HEALTH CENTER IN SURABAYA, INDONESIA - Florentina Sustini; Sundari Indah Wiyasihati; Bella Patricia Simanjorang (Majalah Biomorfologi, 2023)
Highlights1. The Body Mass Index (BMI) measures how much fat the body carries.2. Obesity and overweight are characterized by an excessive buildup of fat that may be detrimental to health. AbstractBackground: Body Mass Index (BMI) is an indicator of body fat. It is classified as underweight, normal, overweight, and obese. Obesity is a risk factor for hypertension (systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg). Objective: To analyze the correlation between BMI with systolic and diastolic blood pressure. Methods: This was an observational research with a cross-sectional design, and the samples consisted of 60 individuals aged 35 to 59 selected using accidental sampling. Blood pressure was the dependent variable whereas BMI was the independent variable. Data were analyzed using Pearson and Spearman correlation tests. Results: There were 44 females (73.3%) and 16 males (26.7%). The largest age groupings were between 45-49 and 50-54 years (31.7%), while the smallest was between 55-59 years (5%). Thirty-three samples (55%) were overweight (>25 kg/m2), 32 samples (53.4%) had systolic blood pressure above normal (≥120 mmHg), and 42 samples (70%) had diastolic blood pressure above normal (≥80 mmHg). The Pearson correlation test between BMI and systolic blood pressure showed a weak correlation (p=0.009 r=0.336). The Spearman correlation test between BMI and diastolic blood pressure showed a weak correlation (p=0.013 r=0.321). Conclusion: There was a weak correlation between BMI with systolic blood pressure, and there was a weak correlation between BMI with diastolic blood pressure in this study.